DZIKIR AS A SUFISTIC MEDITATION TECHNIQUES IN IMPROVING THE QUALITY OF BODY ENERGY - Hanna Aisyah; Naan Naan (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2020)
This paper aims to find out the benefits of sufistic meditation in the form of dhikr on the quality of the subtle (aura) human body. Subtle body quality improvement is influenced by how a person controls the energy centers in the human body. However, not many people know how to control these energy centers. By using qualitative methods, this paper yields the conclusion that dhikr can be used as a way to improve the quality of the subtle body. This is because dhikr is an activity of concentration of mind where the conditions are actually energy centers operating. With constant dhikr, energy centers can operate optimally, which in turn has a good impact on the quality of one's subtle body.